Unraveling the polychromy and antiquity of the Pachacamac Idol, Pacific coast, Peru. - Marcela Sepúlveda; Denise Pozzi-Escot; Rommel Angeles Falcón; Nicolas Bermeo; Matthieu Lebon; Christophe Moulhérat; Philippe Sarrazin; Philippe Walter (PLoS ONE)
Pachacamac is the name of the 15th-16th century Inca sanctuary on the Peruvian coast as well as the name of one of the principal oracles of Inca divinities. This effigy would have been destroyed by Pizarro in 1533 during his visit to the great monumental complex, and as such the originality and antiquity of the wooden statue-the so-called Pachacamac Idol-have been the subject of much controversy and debate. We present here previously unpublished dates that confirm its manufacture during the Middle Horizon (AD 500-1000), as well as evidence of its original polychromy. Traces of colors were observed on its different sections with portable microscopy and analyses with two different X-Ray Fluorescence spectrometry techniques, leading to identification of yellow, white, and red mineral pigments, including the presence of cinnabar. Dated between the 8th and 9th centuries, the statue would have been worshipped for almost 700 years, from the time of its creation to the time of the Spanish conquest, when Pachacamac was a major place of pilgrimage. These data not only offer a new perspective on Pachacamac's emblematic sacred icon, but also on the colorful practices of the Pre-Hispanic Andes.